Social protection for atypical workers during the pandemic: Measures, policy debates and trade union involvement in eight member states - Slavina Spasova; Dalila Ghailani; Sebastiano Sabato; Bart Vanhercke (European Trade Union Institute (ETUI), 2022)
The spread of Covid-19 and the ensuing adoption of lockdown measures have had severe consequences for European labour markets. All EU governments quickly made unprecedented economic and social support available to tackle the consequences of the pandemic. However, these measures - introduced by EU Member States during the pandemic as regards unemployment benefits, sickness benefits and special leave for parents - have not fundamentally improved formal access to social protection schemes for non-standard workers and the self-employed. Especially in the domain of unemployment benefits, temporary (sometimes one-off), mostly flat-rate and means-tested benefits have been introduced for these categories, thus falling short in structurally addressing important gaps in their social protection systems, which pre-date the Covid-19 pandemic. The present report discusses the measures targeted at non-standard workers and the self-employed in eight countries: Belgium, France, Ireland, Italy, Lithuania, Portugal, Romania and Sweden. These case studies confirm the emergency and non-structural character of the measures but also provide innovative country-specific examples. The pandemic has triggered debates on the situation of specific categories of workers and on the need to address gaps in their protection (e.g. workers in the platform economy). It has also highlighted the active role that trade unions have played during the crisis. Nevertheless their involvement in the decision-making process has clearly been uneven across countries and has been dependent on political will and on the state of social dialogue.
Keywords: 330; Arbeitslosenversicherung; Lohnfortzahlung; Elternzeit; Coronavirus; Atypische Beschäftigung; Selbstständige; EU-Staaten